Three-dimensional visualization of the rotavirus hemagglutinin structure - Shaw, A.L. (Cell, 1993)
Three-dimensional structures of a native simian and reassortant rotavirus have been determined by electron cryomicroscopy and computer image processing. The structural features of the native virus confirm that the hemagglutinin spike is a dimer of VP4, substantiated by in vivo radiolabeling studies. Exchange of native VP4 with a bovine strain equivalent results in a poorly infectious reassortant. No VP4 spikes are detected in the three-dimensional reconstruction of the reassortant. The difference map between the two structures reveals a novel large globular domain of VP4 buried within the virion that interacts extensively with the intermediate shell protein, VP6. Our results suggest that assembly of VP4 precedes that of VP7, the major outer shell protein, and that VP4 may play an important role in the receptor recognition and budding process through the rough endoplasmic reticulum during virus maturation.